Cyclophosphamide administration routine in autoimmune rheumatic diseases: a review - Kaian Amorim Teles; Patricia Medeiros-Souza; Francisco Aires Correa Lima; Bruno Gedeon de Araújo; Rodrigo Aires Correa Lima (Revista Brasileira de Reumatologia)
Abstract Cyclophosphamide is an alkylating agent widely used for the treatment of malignant neoplasia and which can be used in the treatment of multiple rheumatic diseases. Medication administration errors may lead to its reduced efficacy or increased drug toxicity. Many errors occur in the administration of injectable drugs. The present study aimed at structuring a routine for cyclophosphamide use, as well as creating a document with pharmacotherapeutic guidelines for the patient. The routine is schematized in three phases: pre-chemotherapy, administration of cyclophosphamide, and post-chemotherapy, taking into account the drugs to be administered before and after cyclophosphamide in order to prevent adverse effects, including nausea and hemorrhagic cystitis. Adverse reactions can alter laboratory tests; thus, this routine included clinical management for changes in white blood cells, platelets, neutrophils, and sodium, including cyclophosphamide dose adjustment in the case of kidney disease. Cyclophosphamide is responsible for other rare - but serious - side effects, for instance, hepatotoxicity, severe hyponatremia and heart failure. Other adverse reactions include hair loss, amenorrhea and menopause. In this routine, we also entered guidelines to post-chemotherapy patients. The compatibility of injectable drugs with the vehicle used has been described, as well as stability and infusion times. The routine aimed at the rational use of cyclophosphamide, with prevention of adverse events and relapse episodes, factors that may burden the health care system.